Incidence of acute respiratory distress syndrome: a comparison of two definitions - Goh, A.Y.; Chan, P.W.; Lum, L.C.; Roziah, M. (BMJ Publishing Group, 1998)
Both definitions identified similar groups of patients. The incidence in this population was higher than that reported elsewhere, but mortality and cause were similar to those in developed countries. Poor outcome was associated with sepsis, a high admission PRISM score, and simultaneous occurrence of other organ dysfunction.